Optimizing Grinding and Regrinding Capacity in Mill Design (40320e24-3686-4866-9cff-ea7a256b0d97) - Robert J. Brison; Robert A. Campbell (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1974)
The problem of optimizing from an economic standpoint the capacity of grinding equipment in the design of a new concentrator is discussed. Although directed specifically to copper flotation mills employing conventional wet, grinding, the material presented is considered applicable with modifications to other types of ores and other grinding methods. A general approach to optimizing the grinding capacity is outlined and illustrated by an example. The' interrelation between grinding capacity and other aspects of the project is considered. The problem of regrind capacity and its relation to preceeding and subsequent processing steps is also discussed. Finally, factors are considered that may, in certain cases, dictate modifications of the suggested approach.